2024
DOI: 10.1038/s41537-023-00424-2
|View full text |Cite
|
Sign up to set email alerts
|

Choroid plexus volume enlargement in first-episode antipsychotic-naïve schizophrenia

Jiaxin Zeng,
Tianwei Zhang,
Biqiu Tang
et al.

Abstract: Investigation of the choroid plexus in schizophrenia has seen growing interest due to its role in the interaction between neuroinflammation and brain dysfunction. Most previous studies included treated and long-term ill patients, while antipsychotics and illness course might both affect the choroid plexus. Here, we recruited first-episode antipsychotic-naïve schizophrenia patients, performed high-resolution structural brain scan and manually extracted choroid plexus volume. Choroid plexus volume was compared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…(2023) observed that a history of childhood trauma significantly moderates the relationship between inflammation and cognitive functioning in FEP ( 74 ). Furthermore, the increased size of the choroid plexus volume in antipsychotic-naïve FEP lends additional support to the significant influence of neuroinflammation on cerebral impairment ( 75 ).…”
Section: Low-level Inflammation and Neuroprogression In Schizophreniamentioning
confidence: 86%
“…(2023) observed that a history of childhood trauma significantly moderates the relationship between inflammation and cognitive functioning in FEP ( 74 ). Furthermore, the increased size of the choroid plexus volume in antipsychotic-naïve FEP lends additional support to the significant influence of neuroinflammation on cerebral impairment ( 75 ).…”
Section: Low-level Inflammation and Neuroprogression In Schizophreniamentioning
confidence: 86%